Referencing geostrophic velocities using ADCP data at 24.5°N (North Atlantic) - Comas-Rodríguez, Isis; Hernández-Guerra, Alonso; McDonagh, Elaine L. (Scientia Marina, 2011)
Acoustic Doppler Current Profilers (ADCPs) have proven to be a useful oceanographic tool in the study of ocean dynamics. Data from D279, a transatlantic hydrographic cruise carried out in spring 2004 along 24.5°N, were processed, and lowered ADCP (LADCP) bottom track data were used to assess the choice of reference velocity for geostrophic calculations. The reference velocities from different combinations of ADCP data were compared to one another and a reference velocity was chosen based on the LADCP data. The barotropic tidal component was subtracted to provide a final reference velocity estimated by LADCP data. The results of the velocity fields are also shown. Further studies involving inverse solutions will include the reference velocity calculated here. Los perfiladores de corriente acústicos Doppler (Acoustic Doppler Current Profiler - ADCPs) son una herramienta oceanográfica útil en el estudio de la dinámica oceánica. Se han procesado los datos de la sección transatlántica a lo largo de 24.5°N, realizada durante la campaña oceanográfica D279 en primavera de 2004, mientras que los datos de ?bottom track? del LADCP (Lowered ADCP) se han empleado en la elección de la velocidad de referencia aplicada a los cálculos geostróficos. Se realizan comparaciones entre los datos obtenidos mediante diferentes combinaciones de ADCP?s. Finalmente, se obtiene una velocidad de referencia final mediante las medidas de LADCP, a las que se resta la componente barotrópica de la marea. Asimismo, se muestran los campos de velocidad resultantes. Estudios futuros incluirán la velocidad de referencia calculada en la obtención de resultados mediante modelos inversos. 338 331 1,079 Q3 SCIE